Review and analysis of over 40 years of space plant growth systems. (August 2016) - Zabel, P.; Bamsey, M.; Schubert, D.; Tajmar, M.
Abstract: The cultivation of higher plants occupies an essential role within bio-regenerative life support systems. It contributes to all major functional aspects by closing the different loops in a habitat like food production, CO2 reduction, O2 production, waste recycling and water management. Fresh crops are also expected to have a positive impact on crew psychological health. Plant material was first launched into orbit on unmanned vehicles as early as the 1960s. Since then, more than a dozen different plant cultivation experiments have been flown on crewed vehicles beginning with the launch of Oasis 1, in 1971. Continuous subsystem improvements and increasing knowledge of plant response to the spaceflight environment has led to the design of Veggie and the Advanced Plant Habitat, the latest in the series of plant growth systems. The paper reviews the different designs and technological solutions implemented in higher plant flight experiments. Using these analyses a comprehensive comparison is compiled to illustrate the development trends of controlled environment agriculture technologies in bio-regenerative life support systems, enabling future human long-duration missions into the solar system.